Ecotoxicology : (Levis, tieur suwr tacs giar, 1996)
A unique presentation that unifies the field, this book brings together concepts and information about contaminant effects at all levels of the biological hierarchy. Beginning at the biomolecular level, this book builds progressively toward a discussion of effects to the global biosphere. Emphasizing ecological components and fundamental paradigms, the authors strike a balance between the presentation of details relevant at each level and the integration of phenomena and processes among levels. A milestone in the field, the book is suitable for graduate courses, as well as a reference for professionals in the field.